In vitro Inhibitory Action of Honey Against Extended Spectrum β-Lactamase Producing Escherichia coli and Klebsiella pneumoniae - Kayastha, Supriya; Awal, Bal Krishna; K.C., Sudeep; Khanal, Santosh; Joshi, Tista Prasai; Joshi, Dev Raj (Journal of Nepal Biotechnology Association, 2026)
Antibiotic resistant Gram-negative bacteria, in particular, extended spectrum β-lactamase (ESBL) producing Escherichia coli and Klebsiella pneumoniae are frequently involved in various human infections. Despite traditional applications of honey, a comprehensive evaluation of antimicrobial activity against ESBL-producing bacteria is lacking. This study aims to evaluate the antibacterial activity of honey against ESBL-producing and non-producing bacteria isolated from clinical samples (urine and sputum) by tube dilution method and the time kill viability assay. The minimum inhibitory concentration (MIC) of honey was found to be 25% (v/v) against most of E. coli (13 out of 18 isolates were inhibited by both indigenous and Dabur honey) and 50% (v/v) against most of K. pneumoniae (10 and 11 out of 14 isolates inhibited by indigenous and Dabur honey respectively). The MIC of honey for ESBL-producing and non-producing bacteria was found to be almost similar (p > 0.05). The complete reduction of bacterial population (8 log10 CFU/ml) was observed after 24 hours of exposure to honey at 50% (v/v) concentration. The honey samples showed bacteriostatic and bactericidal activity against tested isolates of ESBL-producing and non-producing E. coli and K. pneumoniae. These findings suggested indigenous honey serve as a promising complementary therapeutic agent in managing resistant bacterial infections.